Improvements in motor control are associated with improved quality of life following an at-home muscle biofeedback program for chronic stroke - Marin-Pardo, Octavio; Donnelly, Miranda Rennie; Phanord, Coralie S.; Wong, Kira; Liew, Sook-Lei (Frontiers in Human Neuroscience, 2024)
Chronic stroke survivors with severe arm impairment have limited options for effective rehabilitation. High-intensity, repetitive task practice (RTP) is known to improve upper limb function among stroke survivors with residual movement. However, clients without volitional movement are ineligible for RTP-based interventions and require hands-on facilitation from a clinician. Alternatively, at-home telerehabilitation using muscle biofeedback may provide a more accessible and effective option for survivors with severe impairment and could potentially help them regain enough volitional activation to be eligible for other therapies. Specifically, training to reduce unintended muscle coactivation using electromyography (EMG) biofeedback may modestly improve motor control in people with limited movement. Importantly, these functional changes may influence the perceived impact of stroke-related disability in daily life. In this manuscript, we examine whether physical changes following use of a portable EMG biofeedback system (Tele-REINVENT) for severe upper limb hemiparesis also relate to perceived quality of life improvements. Secondarily, we examined the effects of Tele-REINVENT, which transforms individuated muscle activity into computer game control, on different domains of stroke recovery. For this pilot study, nine stroke survivors with chronic impairment (Fugl-Meyer = 14-40/66) completed 30 1-hour sessions of home-based training. To assess motor control and performance, we measured changes in active wrist ranges of motion, the Fugl-Meyer Assessment, the Action Research Arm Test, and an EMG-based test. To examine changes in perceived quality of life, we utilized the Stroke Impact Scale and participant feedback. Our results suggest that remote training can induce modest changes on clinical and functional assessments, improving active wrist ranges of motion. Additionally, changes in motor control were correlated with the perceived impact of stroke on participation and physical abilities. We also report changes in corticomuscular coherence, showing a laterality change from the ipsilesional to the contralesional motor cortex during wrist extension. Overall, our results suggest that Tele-REINVENT represents a promising telerehabilitation intervention that might improve sensorimotor outcomes in severe chronic stroke, and that improving sensorimotor abilities even modestly may improve quality of life. We propose that Tele-REINVENT may be used as a precursor to help participants gain enough active movement to participate other occupational therapy interventions.